PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH - I Nyoman Bayu Pramartha; Ni Putu Yuniarika Parwati (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
History is not a subject only taught at the school level. History is the path to a more realistic understanding. This historical reality indicates that history learning is very relevant to be taught and integrated to the nation's future generations. History is not just a useless past story, but history is evidence of events that are reality and very useful for shaping the generation of characters for the nation's future generations. This study aims to analyze the implementation of character education in the learning process of history subjects.